مسلم معاشروں میں مغربی تہذیب کے اثرات اور ٹرانس جینڈر ایکٹ: ایک تنقیدی جائزہ: Impact of Western Civilization in Muslim Societies and Transgender Act: A Critical View - Dr. Farhat Naseem Alvi; Dr. Abdul Manan Cheema (Al Basirah, 2024)
Western culture is dominating rapidly in Muslim societies in current times. Islamic social values are being marginalized gradually. Impact of Western thought, in this regard, on Muslim world seems to be a challenge for Muslim scholars. The entire world has been converted into global village because of advance technology and communication. In this global age, Muslim youth is adopting western secular lifestyle. From materialistic aspects, the West is stronger economically, but socially it is weaker than the Muslim culture and civilization. Therefore, the foundations of Islamic social system are being overwhelmed by the West. Western thought manures in the disguise of attractive slogans of human rights, women rights, transgender rights, feminism, enlightenment, equality, and freedom. Recently, an LGBT+ Movie Joy land (2022) was produced in Pakistan. The basic aim was to promote western civilization in this Islamic country. The main objective of this research article is to highlight practice of western thought and culture in Muslim societies that is destabilizing bases of Islamic social system. Seemingly it becomes our responsibility to play our role in contesting emerging trends of western civilization in Muslim societies.